Does village fund audit affect village development? An empirical study of villages in Aceh Province - Helmi, Sayid Reza; Khoirunurrofik, Khoirunurrofik (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
It is well-known that additional cases of misappropriating village funds are reported yearly. Without adequate oversight and control, the fraud and corruption trends in village funds will continue to prevail and hinder village development. The increase of funds transferred to villages has failed to eliminate the number of underdeveloped villages in Indonesia, which is still 24.39% nationally and 36,15% in Aceh Province. This study examined whether the local government's audit of village funds positively affects village development as measured by the Village Development Index (IDM) value. The relationship between audits, the number of auditors, and audit fees on village development is examined using a quantitative approach and the regression method. A qualitative technique was also used to gain insights into the implementation of village fund audits. The study found a positive relationship between auditing and audit fees for IDM, while the number of auditors is unrelated to IDM. Compared to unaudited villages, audited villages have higher IDM scores. Despite having a good relationship, the implementation of the audit faced challenges, among others, the lack of legislation, the absence of auditing and accounting standards, the auditor's ambiguous authority, the scarcity of audit resources, and the local government's recklessness in performing their duties.